Targeting the RNA demethylase FTO for cancer therapy. Issue 5 (6th August 2021) - Zhou, Lin-Lin; Xu, Hongjiao; Huang, Yue; Yang, Cai-Guang
Abstract : Chemical modulation of the RNA m 6 A demethylase FTO for cancer therapy. Abstract : N 6 -Methyladenosine (m 6 A) is the most prevalent internal modification on mRNA and represents a new layer of gene expression in eukaryotes. The field of m 6 A-encoded epitranscriptomics was rejuvenated with the discovery of fat mass and obesity-associated protein (FTO) as the first m 6 A demethylase responsible for RNA modification in cells. Increasing evidence has revealed that FTO is significantly involved in physiological processes, and its dysregulation is implicated in various human diseases. Considering this functional significance, developing small-molecule modulators of the FTO protein represents a novel direction for biology research. However, such modulators remain in the early stages of development. Here, our review mainly focuses on the progress of FTO inhibitor development to date. We summarize screening methods used to identify FTO modulators, techniques used to assess the biological effects of these modulators, strategies used to achieve selective inhibition of FTO rather than its homologues, and the results of investigations of FTO modulator modes of action and anticancer efficacy. Thus, this review aims to facilitate novel chemical entity discovery, probe FTO biology, and promote the validation of FTO as a clinical drug target for cancer treatment.